More microbial manipulation and plant defense than soil fertility for biochar in food production: A field experiment of replanted ginseng with different biochars - Liu, Cheng; Xia, Rong; Tang, Man; Liu, Xiaoyu; Bian, Rongjun; Yang, Li; Zheng, Jufeng; Cheng, Kun; Zhang, Xuhui; Drosos, Marios; Li, Lianqing; Shan, Shengdao; et al. (Frontiers in Microbiology, 2022)
The role of biochar-microbe interaction in plant rhizosphere mediating soil-borne disease suppression has been poorly understood for plant health in field conditions. Chinese ginseng (Panax ginseng C. A. Meyer) is widely cultivated in Alfisols across Northeast China, being often stressed severely by pathogenic diseases. In this study, topsoil of a continuously cropped ginseng farm was amended at 20 t ha-1 respectively with manure biochar (PB), wood biochar (WB) and maize residue biochar (MB) in comparison to conventional manure compost (MC). Post-amendment changes in edaphic properties of bulk topsoil and the rhizosphere, in root growth and quality and in disease incidence were examined with field observations and physicochemical, molecular and biochemical assays. Three years following amendment, increases over MC in root biomass was parallel to the overall fertility improvement, being greater with MB and WB than with PB. Differently, survival rate of ginseng plants increased insignificantly with PB but significantly with WB (14%) and MB (21%) while ginseng root quality unchanged with WB but improved with PB (32%) and MB (56%). For the rhizosphere at harvest following three years growing, total content of phenolic acids from root exudate decreased by 56%, 35% and 45% with PB, WB and MB respectively over MC. For rhizosphere microbiome, total fungal and bacterial abundance was both unchanged under WB but significantly increased under MB (by 200% and 38%), respectively over MC. At phyla level, abundances of arbuscular mycorrhizal and Bryobacter as potentially beneficial microbes was elevated while those of Fusarium and Ilyonectria as potentially pathogenic microbes reduced, with WB and MB over MC. Moreover, rhizosphere fungal network complexity was enhanced insignificantly under PB but significantly under WB moderately and MB greatly, over MC. Overall, maize biochar exerted great impact rather on rhizosphere microbial community composition and networking of functional groups, particularly of fungi, and thus plant defense than on soil fertility and root growth.